Nurse managers’ perceptions of the competence of newly graduated nurses: A scoping review - Kukkonen Pia; Leino‐Kilpi Helena; Koskinen Sanna; Salminen Leena; Strandell‐Laine Camilla (Wiley, 2022)
Aim
To summarise nurse managers’ perceptions of newly graduated nurses’ (NGNs) competence and connected factors.
Background
Nurse managers recruiting staff are responsible for employing competent nurses to ensure quality care and professional standards. Knowledge of managers’ perceptions about the competence of NGNs is needed to understand the expectations of the health care system towards future professionals.
Evaluation
A scoping review was conducted. A total of 12 research publications met the inclusion criteria and were analysed using inductive content analysis.
Key issues
Managers’ perceptions can be divided into three perspectives: NGNs’ competence descriptions, assessment of competences, and connected factors. The NGNs’ level of competence was assessed to be at least satisfactory, and dependent on prior exposure to the work setting, change in the degree of responsibility, and lack of confidence.
Conclusion
Existing knowledge about nurse managers’ perceptions of NGNs’ competence is limited and rather fragmented. There is a clear need for rigorous empirical studies with comprehensive views of managers, emphasising the key role of managers in the evaluation of nurse competence.